107 Plaque composition and plaque volume in non-stented vessels determines serum biomarker levels after stenting in stable angina: a VH-IVUS study. (22nd September 2015) - Calvert, P A; Obaid, D R; Malhotra, A; West, N E J; Shapiro, L M; McNab, D; Densem, C G; Schofield, P M; Braganza, D; Clarke, S C; Ray, K R; O'Sullivan, M; et al.
Abstract : Introduction: Previous work has shown that plaque composition in stented vessels determined by virtual histology intravascular ultrasound (VH-IVUS) predicts myocardial necrosis after percutaneous coronary intervention (PCI). However, disease in non-stented vessels may also determine myocardial necrosis, for example, reduced collateral blood flow may increase the area of myocardial necrosis after PCI. We examined whether plaque composition or volume (determined by VH-IVUS) in non-stented vessels or the whole coronary tree contributed to stenting-related rises in serum biomarkers. Methods: Hundred patients with stable angina, referred for elective PCI underwent full 3-vessel VH-IVUS. Serum Troponin-I, interleukin-6 (IL-6), and high-sensitivity C-reactive protein (hsCRP) were measured before and 24 h after PCI. Troponin-I and hsCRP results were logarithmically transformed (log10 ) to a normal distribution to permit calculation of Pearson's correlation coefficient. Results: In stable angina patients, there was no significant difference in total plaque volume (563±60 mm 3 vs 632±62 mm 3 respectively, mean±SEM p=0.42), nor in necrotic core volume (NC) (73±13 mm 3 vs 61±10 mm 3 respectively, p=0.48) between stented and non-stented vessels. After PCI for stable angina the biomarker levels were: troponin-I: 0.27 ng/ml (0.06–0.94 ng/ml), IL-6: 8.0 pg/ml (5.5–11.4 pg/ml) and hsCRP: 5.7 mg/l (3.4–10.0 mg/l) (median (IQR)). Troponin-I levels correlated with total NC and total plaque volume on 3-vessel VH-IVUS (r=0.45, p=0.003; r=0.417, p=0.006 respectively), and in non-stented vessels (NC vs troponin-I: r=0.423, p=0.006; plaque volume vs troponin-I: r=0.37, p=0.018). However there was no correlation between troponin-I and either NC or plaque volume in the stented vessels (p=0.2 and p=0.45 respectively). Similarly, serum IL-6 correlated with both NC and plaque volume on 3-vessel VH-IVUS (r=0.414, p=0.009; r=0.412, p=0.009 respectively) and in non-stented vessels (r=0.47, p=0.003; r=0.376, p=0.003 respectively). However, there was no correlation between IL-6 and NC or plaque volume in stented vessels (p=0.33 and p=0.47 respectively). There were no significant correlations between VH-IVUS parameters and hsCRP. Adjusting for plaque volume the correlation between the 3-vessel NC/total plaque volume ratio and IL-6 remained (r=0.329, p=0.044) but not between 3-vessel NC/plaque volume ratio and troponin-I (p=0.23). Although Troponin-I rise correlated with total length of stents implanted (r=0.36, p=0.002), IL-6 and hsCRP did not (p=0.41 and p=0.94 respectively). Conclusion: Three-vessel and non-stented vessel plaque composition and plaque volume determined by VH-IVUS correlate with troponin-I and IL-6 levels after PCI for stable angina, whereas plaque composition or plaque volume of the stented vessel do not. This difference highlights the importance of disease in non-stented vessels in PCI-related myocardial necrosis.